Company perspectives from Trinidad and Tobago on renewable energy management systems and energy efficiencies - Natasha Ramkissoon-Babwah; Septin Puji Astuti (Center for Science and Technology, IAIN Surakarta, 2021)
The global energy market is currently undergoing a transformation at all levels within their supply chains as there is a gradual shift from the fossil fuel paradigm towards sustainable renewable energy (RE) sources and energy efficiencies (EEs). This research study examines this issue by employing an empirical research process. A survey was undertaken with fifty companies operating in Trinidad and Tobago and investigated their interest in adopting RE management systems and EEs. The research revealed that most of the companies have a low level of interest in RE management systems primarily because of current low energy costs for their operations and limited knowledge about current public sector energy incentives. To ameliorate this situation, educational campaigns, training package development, and complementary energy workshops are suggested to motivate and encourage business enterprises to consider the EE pathway.